Tanggungjawab Notaris Terhadap Akta Otentik Yang Penghadapnya Mempergunakan Identitas Palsu Di Kota Pekanbaru - Rahmad Hendra (Jurnal Ilmu Hukum, 2012)
Notary is a defender of truth and justice so that law enforcement should be run in good faith and sincerity, so that the legal profession is an honorable and noble profession (officium nobile). The number of notaries create tighter competition between notaries and notary sometimes make less careful in their profession. The paper concludes that the notary is responsible for what he saw, that they have seen, heard and done by the notary as a public official in the run position. Notaries are not responsible if any information and documents from a client that is not true.